2022
DOI: 10.1039/d2dt00312k
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally dynamic copper coordination complexes

Abstract: The interplay between oxidation state and coordination geometry dictates both kinetic and thermodynamic properties underlying electron transfer events in copper complexes. An ability to stabilize both CuI and CuII oxidation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(59 citation statements)
references
References 48 publications
9
46
1
Order By: Relevance
“…The Cu–N pyr bonds shorten slightly to 1.994(2) and 1.990(2) Å, while the Cu–N2 contact contracts significantly to 2.094(2) Å upon oxidation (Table ). This contraction of nearly 0.4 Å is consistent with similar phenomena observed in Cu I/II tripicolylamine systems, and overall, the bond lengths are similar to other reported cupric chloride dipicolylanisidines. , The complex has a τ 5 = 0.13 using the geometry index proposed by Addison and Reedijk for five-coordinate complexes, consistent with a slightly distorted square pyramidal geometry …”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The Cu–N pyr bonds shorten slightly to 1.994(2) and 1.990(2) Å, while the Cu–N2 contact contracts significantly to 2.094(2) Å upon oxidation (Table ). This contraction of nearly 0.4 Å is consistent with similar phenomena observed in Cu I/II tripicolylamine systems, and overall, the bond lengths are similar to other reported cupric chloride dipicolylanisidines. , The complex has a τ 5 = 0.13 using the geometry index proposed by Addison and Reedijk for five-coordinate complexes, consistent with a slightly distorted square pyramidal geometry …”
Section: Resultssupporting
confidence: 88%
“…However, synthesis using CuCl provided an inner-sphere chloride ligand that enabled the isolation of stable CuCl­(dpaa OMe ) and CuCl­(dpaa H ) complexes (Chart b). Similar to the CuCl­(dpa R ) complexes reported in ref , elemental analysis revealed that in the solid state, the CuCl­(dpaa OMe ) complex can exist as a μ-Cl bridging dimer with the formula {[Cu­(dpaa OMe )] 2 (μ-Cl)}­{CuCl 2 }.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations